Rancang Bangun Sistem Deteksi Dan Monitoring Kekeruhan Air Menggunakan Microcontroller Arduino Berbasis Internet Of Things - Sidik, Muhamad; Siswanto, Eko (MEANS (Media Informasi Analisa dan Sistem), 2020)
ABSTRACTA water reservoir, located in Kudu Baru  Genuk resident Semarang, is managed to meet the daily water needs of residents of RT 01 RW 06. It is namely Kudu Baru  Water Supply and Sanitation (WSS). The water reservoir has a capacity of 6900 liters of water, consisting of 2 water reservoir and has 120 customers in the WSS Kudu Baru  area. The problem that exists in WSS Kudu Baru  is the lack of control and cleaning of water reservoirs regularly so that there is no early prevention of automatic notification to residents if the water in the reservoir is muddy or dirty. Due to this problem, the turbid water flows into the residents' houses. Making a water turbidity detection and monitoring system using a TDS-10 sensor installed in a water reservoir connected to an Arduino device engages the use of  C programming language. IOT (Internet Of Thinks) in this study is used to store tendon water turbidity data for monitoring.